THE INFLUENCE OF DOXING ON THE DEVELOPMENT OF CYBERCRIME THROUGH WHATSAPP IN A CRIMINALISTIC PERSPECTIVE - Muhammad Ikhsan Khairi; Chairuni Nasution (PT. Radja Intercontinental Publishing, 2026)
The development of information and communication technology has brought significant changes to people's interaction patterns, especially through the use of social media and instant messaging applications such as WhatsApp. On the other hand, these advances are also various forms of cybercrime, one of which is doxing. Doxing is the act of collecting, disclosing and disseminating a person's personal data without legal consent, which has the potential to cause serious harm to the victim. From a criminalistic perspective, doxing is not only understood as a violation of the law, but also as a criminal event that leaves a digital footprint that can be analyzed scientifically for the sake of legal proof. This study aims to examine the juridical regulation of cybercrime in Indonesian criminal law and analyze the influence of doxing in the development of cybercrime through WhatsApp. The research method used is normative juridical research with a literature approach. The results of the study show that although doxing has not been explicitly regulated as a separate offense, the act can be charged through the provisions of the Electronic Information and Transaction Law and the Personal Data Protection Law. Therefore, it is necessary to strengthen regulations and increase criminalistic understanding to deal with the increasingly complex phenomenon of doxing